The agreement establishing a unified patent court and its impact on the Brussels I Recast Regulation. The new rules introduced under Regulation (EU) no 542/2014 in respect of the Unified Patent Court and the Benelux Court of Justice - Marongiu Buonaiuti, Fabrizio (CUADERNOS DE DERECHO TRANSNACIONAL, 2016)
The present study deals with the agreement establishing a Unified Patent Court (UPC), signed by 25 EU Member States on 19 February 2013 and its impact on the rules on jurisdiction in civil and commercial matters as contained in Regulation (EU) No. 1215/2012 (s.c. “Brussels I Recast Regulation”), which replaces the pre-existing Brussels I Regulation. The study analyses the new rules introduced in the Brussels I Recast Regulation through Regulation (EU) No 542/2014, making provision for the application of the rules on jurisdiction as contained in the Regulation to the UPC as well as to the Benelux Court of Justice, as judicial bodies common to several Member States. As concerns the UPC, the new rules introduced by Regulation No 542/2014 appear welcome, insofar as they provide for the enlargement of the territorial scope of the competence of the UPC itself, a competence that the agreement itself considers as exclusive. Nonetheless, the new rules fall short of addressing effectively the problems of coordination of the exclusive jurisdiction provided for under Article 24.4 of the Brussels I Recast Regulation in respect of actions concerning registration or validity of intellectual property rights, including European patents, with other heads of jurisdiction such as that provided for under Art. 7.2 of the same Regulation in respect of actions in matters of tort or delict, such as those concerning the infringement of the same rights. Keywords: Unified Patent Court, courts common to several Member States, Brussels I Recast Regulation, jurisdiction in civil and commercial matters, conflicts of jurisdiction. Riassunto: Lo scritto esamina l’accordo istitutivo del Tribunale unificato dei brevetti, firmato da 25 Stati Membri dell’UE il 19 febbraio 2013 e la sua incidenza sulla disciplina della competenza giurisdizionale in materia civile e commerciale contenuta nel regolamento n. 1215/2012 (c. d. Bruxelles Ibis”), che sostituisce il precedente regolamento Bruxelles I. Lo scritto si sofferma sulle nuove disposizioni inserite nel regolamento Bruxelles I-bis mediante il regolamento n. 542/2014, relativo all’applicazione delle regole contenute nel regolamento n. 1215/2012 al Tribunale unificato dei brevetti e alla Corte di giustizia del Benelux, quali organi giurisdizionali comuni a più Stati membri. Per quanto riguarda il Tribunale unificato dei brevetti, le nuove disposizioni appaiono opportune nella misura in cui comportano un’estensione ratione loci della competenza del Tribunale, competenza la quale presenta carattere esclusivo. Nondimeno, le nuove disposizioni presentano il limite di non affrontare adeguatamente i problema di coordinamento della giurisdizione esclusiva prevista dall’art. 24, n. 4, del regolamento Bruxelles I-bis rispetto alle azioni concernenti la registrazione o la validità dei diritti di proprietà intellettuale, inclusi i brevetti europei, con altri criteri di giurisdizione come quello previsto dall’art. 7, n. 2, del regolamento per le azioni in materia di illeciti civili, come quelle concernenti la violazione dei diritti in questione. Parole chiave: Tribunale unificato dei brevetti, Organi giurisdizionali comuni a più Stati Membri, Regolamento Bruxelles I-bis, Giurisdizione in materia civile e commerciale, Conflitti di giurisdizione.